(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
An individual is a member of a particular society. In order to become a person,a person must be spiritually developed, distinguished by his own characteristics and qualities. The development of a person begins, first of all, with the formation of his personal qualities.Education and science play and important role in a person’s activities. Because of this, a person becomes a great person